I love you, mouse - Graham, John, 1926-; De Paola, Tomie (New York : Harcourt Brace Jovanovich, 1978)
A child imagines the things he would do with various animals if he were one of them.
3.3
K-3
Keywords: Animals -- Fiction; Animals -- Fiction